Compaction assessment of recycled aggregates for use in unbound subbase application - Ayan, Vahid; Limbachiya, Mukesh C.; Omer, Joshua R.; Azadani, Seyyed Masoud Nasr (Journal of Civil Engineering and Management, 2014)
Study was recently conducted at Kingston University to assess the suitability of using recycled concrete aggregate (RCA) and reclaimed asphalt pavement (RAP) in unbound subbase mixtures. The results showed that the use of 100% recycled aggregates increased the optimum moisture content and decreased the maximum dry density of the sub-base materials in comparison with natural aggregates. Moreover, the replacement of RCA by reclaimed asphalt pavement by 50% decreased the optimum moisture content and increased the maximum dry density in proportion to 100% RCA. The effects of physical properties on 0% air void and compaction curve were discussed for each type of subbase. The CBR values of the subbase materials prepared with 100%RCA is lower than subbase mixture with 100% natural aggregates. The CBR further decreased for replaced subbase with RAP so that 50%RCA + 50%RAP is not suitable for unbound subbase from the point of CBR view. In each mix the trend of CBR value was investigated in terms of water content. This research found some significant practical points to use in site works.